Digestive bleeding in children - Ana Barbarita Navarro Sombert; Graciela Goire Herrera; Ledicel Nilo Gámez Fonts; Luis Antonio García Rodríguez (Medisur)
Usually gastrointestinal bleeding doesn't have serious consequences in children, although the newborns and infants are more vulnerable to it. It can appear to any age, with more incidence of acute lesions of gastric and duodenal mucous in bleeding of upper gastrointestinal tract, and fissures and polyps in lower gastrointestinal tract causes. The most serious bleedings are secondary to esophageal varices and Meckel's diverticulum. A good clinical trial, supported by image and endoscopic tests, and standardized therapy, are the key elements for the reduction of mortality in these patients. We presented the Good Clinical Practices Guideline for Gastrointestinal bleeding, approved by consensus in the the 4th National Good Clinical Practices Workshop in Pediatric Surgery (Las Tunas, Cuba; March 2005)